A novel room-temperature formaldehyde gas sensor based on walnut-like WO3 modification on Ni–graphene composites - Mehmood, Shahid; Khan, Faheem Ullah; Shah, Muhmmad Naeem; Ma, Junxian; Yang, Yatao; Li, Guijun; Xu, Wei; Zhao, Xiaojin; He, Wei; Pan, Xiaofang (Frontiers in Chemistry, 2022)
Ternary composite with great modulation of electron transfers has attracted a lot of attention from the field of high-performance room-temperature (RT) gas sensing. Herein, walnut-like WO3-Ni–graphene ternary composites were successfully synthesized by the hydrothermal method for formaldehyde (HCHO) sensing at RT. The structural and morphological analyses were carried out by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). SEM and TEM studies confirmed that walnut-like WO3 nanostructures with an average size of 53 ± 23 nm were functionalized. The Raman and XPS results revealed that, due to the deformation of the O-W-O lattice, surface oxygen vacancies Ov and surface-adsorbed oxygen species Oc were present. The gas-sensing measurement shows that the response of the WO3-Ni-Gr composite (86.8%) was higher than that of the Ni-Gr composite (22.7%) for 500 ppm HCHO at RT. Gas-sensing enhancement can be attributed to a p-n heterojunction formation between WO3 and Ni-Gr, Oc, spill-over effect of Ni decoration, and a special walnut-like structure. Moreover, long term stability (%R = 61.41 ± 1.66) for 30 days and high selectivity in the presence of other gases against HCHO suggested that the proposed sensor could be an ideal candidate for future commercial HCHO-sensing in a real environment.